Songs in the dust: Riel Music in the Northern and Western Cape, South Africa - Britz, Engela (College of Music, 2020)
The centuries-old southern African dance form called rieldans (reel dance), or simply riel (reel), is believed to have emerged from Khoe-San dances. It is characterised by its distinctive footwork, animal mimicry, and courtship displays. In the post-apartheid, postcolonial South African context, the riel has emerged as symbol of indigeneity through largescale public performance of Khoe-San heritage. Despite colonial influences, it represents an historical link to the Khoe-San people for its performers who are, for the most part, persons of mixed descent who were classified as 'coloured’ under colonialism and apartheid. Due to a recent riel revival, which emerged from the alignment of Khoe-San and Afrikaans identity negotiations following democracy, the riel has attracted a fair amount of informal attention both locally and internationally over the last decade. However, it remains largely unexplored in performance scholarship. This study investigates riel music of the Northern and Western Cape Provinces of South Africa. The research is qualitative in nature with data collection through participant-observation, semi-structured interviews (including feedback interviews), archival and literature-based research, and organology. A brief history of the riel is presented through a synthesis of documentary evidence and oral history gleaned from fieldwork. This includes an investigation into the history of the ramkie - an instrument that is strongly associated with the riel. By drawing on emic interpretations of riel music in conjunction with Muller’s and Impey’s ideas about 'music as archive’, this study explores how riel music is an oral/aural archive of indigenous knowledge, memory and experience. Findings indicate that contemporary practice links the riel to pre-colonial Khoe-San practices from which it may have derived. An examination of the ramkie’s history reveals that it emerged from material and cultural exchanges in the Indian Ocean that link southern Africa to a vast trade network in pre-colonial and colonial times. Moreover, the instrument provides a glimpse into gender issues that influence riel music making. Like the dance that it accompanies, riel music exhibits characteristics that are indicative of its Khoe-San influence. An analysis of the liedjies (songs) shows that they deal mostly with themes of romance, place, and death and suffering, and that the music is a powerful platform for the expression of interpersonal concerns that provide a glimpse into the lived experiences of working-class coloured communities in the rural Cape.